Levantamento e manejo de nematoides fitoparasitas em áreas cultivadas com olerícolas na região Centro-Oeste do Estado de São Paulo - Gonçalves, Lucivane Aparecida [UNESP] (2014)
The vegetable crop has great commercial value in the state of São Paulo, and the midwest region a leading producer of vegetable crops such as peppers, tomatoes, cucumbers, among other. Their importance, these crops began to be conducted in a protected environment, however, it favored an increase in problems with nematodes, especially those of the genus Meloidogyne, the most important in vegetable crops. The aim of this research was to nematodes survey in areas cultivated with vegetable crops in the midwest region of São Paulo, focusing on the detection of species of the genus Meloidogyne spp. with emphasis on the detection of M. enterolobii; and evaluate the efficiency of fermented rice bran as an alternative method to control nematodes. The nematodes survey was conducted in 72 vegetable crops producing areas of 29 properties in the midwest of São Paulo. 47 greenhouses with chili, nine with tomato, nine with cucumber, four with American pepper, one with pumpkin and one with salsa were sampled. An area of open cultivation of bean pods and tomato were also sampled. To evaluate the efficiency of fermented rice was previously quantified the population of root-knot nematode, sampling 54 points, collecting soil and root in greenhouse cultivated with hybrid 'Sandy' (CV), and 51 points in greenhouse cultivated with 13 lines of hybrid 'Sandy' and four lines with hybrid 'Lucca' (CV B). The fermented rice bran was composed of 500 liters of water, 25 kg of rice bran and 15 kg of molasses. The CV A were made four applications fermented and CV B, 10 applications. The areas were sampled again seven days after the last application. In the survey, all samples showed nematode parasites of plants, namely, Meloidogyne incognita, M. enterolobii, Rotylenchulus reniformis, Pratylenchus brachyurus, Helicotylenchus sp., ...